Non-destructive broadband terahertz spectroscopy for investigating degradation of poly(2-ethylcyanoacrylic) adhesive. Issue 15 (28th February 2020) - Ariyoshi, Seiichiro; Setyawan, Budi; Hashimoto, Satoru; Negishi, Shun; Mikami, Hikaru; Hiroshiba, Nobuya
Abstract : We apply Fourier-transform terahertz spectroscopy to investigate the deformation of poly(2-ethylcyanoacrylic) adhesive (PECA) on a polyethylene substrate. Abstract : We apply Fourier-transform terahertz spectroscopy to investigate the deformation of poly(2-ethylcyanoacrylic) adhesive (PECA) on a polyethylene substrate. The terahertz absorption spectra of the PECA samples were measured over the frequency range 1–10 THz, and absorption peaks from the adhesive layer were identified at 5.70, 6.23, and 7.55–9.12 THz. The PECA samples were then degraded via a hydration reaction, with the terahertz spectra showing a decrease in the intensity of the main peaks of PECA with increasing water degradation time. This study demonstrates the potential of terahertz spectroscopy for the continuous monitoring of the degradation of an adhesive layer.